Theoretical and Experimental Testing of the Factors of Mortar Projectiles Trajectory for a New Fire Control System - Grzegorz LEŚNIK (Badania teoretyczno-eksperymentalne czynników toru pocisków moździerzowych na użytek nowo opracowywanego systemu kierowania ogniem, 2016)
The paper presents the results of theoretical and experimental tests aimed at developing sets of data. These sets are necessary for compiling firing tables and the operating algorithm for the ballistic computer of a fire control system intended for the mortar system currently used by the Polish Armed Forces as well as the mortar system currently under development. Economy, time saving and the development of numerical methods justify the use of computer simulations for the process of developing software for fire control systems. The theoretical results can only be used for this purpose if their level of compliance with experimental results of live fire tests is acceptable.
Keywords: Balistyka zewnętrzna pocisków moździerzowych